Islamic Values-based Sex Education to Prevent Loss Generation for Senior High School Students - Faidah, Mutimmatul; Rusmanto, Hery; Rahmawati, Lilik (Universitas Islam Negeri Raden Intan Lampung, 2020)
Teenagers’ behavior problems such as free sex, abortion, pornography, and drug abuse have increased in developing countries. The purposes of this research were to formulate the views of experts, education practitioners, and teenagers about the importance of teaching sex education (SE) in schools and to formulate the prototype of sex education, material, media, and learning strategies. This research was a descriptive research. The data was obtained through interviews to reveal experts’ views. The sources of data in this research were teachers, principals, psychologists, scholars, reproductive experts, and sociologists. The data were analyzed using content analysis. A questionnaire was used to find out the students' opinions. The population of this study was the senior high school students in Surabaya, Indonesia. The samples taken were 171 students. The data taken from the questionnaire were analyzed descriptively. The percentage was obtained from the number of respondents who chose ”Agree” and then divided by the number of ”Disagree” of each statement. The results of this research reveal that sex education is expected to provide an understanding of sexuality, the formation of responsible self-attitudes, society, and religion in overcoming sexual turmoil, as well as the skills to avoid promiscuity. Sex education should be given within an ethical and religious framework. Sex education materials include social ethics, the effects of promiscuity, abortion and its effects, and marriage. The media used were films, multimedia, and other media within the framework of Islamic ethics. This research concludes that sex education is important to students, especially high school students.